Portal Inflow Modulation by Somatostatin After Major Liver Resection: A Pilot Study. Issue 6 (June 2018) - Rhaiem, Rami; Piardi, Tullio; Chetboun, Mikael; Pessaux, Patrick; Lestra, Thibaut; Memeo, Riccardo; Kianmanesh, Reza; Sommacale, Daniele
Abstract : N/A: Major hepatectomy (MH) can lead to an increasing portal vein pressure (PVP) and to lesions of the hepatic parenchyma. Several reports have assessed the deleterious effect of a high posthepatectomy PVP on the postoperative course of MH. Thus, several surgical modalities of portal inflow modulation (PIM) have been described. As for pharmacological modalities, experimental studies showed a potential efficiency of Somatostatin to reduce PVP and flow. To our knowledge, no previous clinical reports of PIM using somatostatin are available. Herein, we report the results of PIM using somatostatin in 10 patients who underwent MH with post-hepatectomy PVP > 20 mmHg. Our results suggest Somatostatin could be considered as an efficient reversible PIM when PVP decrease is above 2.5 mmHg.